Vascular calcification in breast and its association with atherosclerosis in common carotid artery - Jha, Anamika; Ghimire, Rabin Kumar; Lohani, Benu; Jha, Sujit Kumar (Grande Medical Journal, 2021)
Introduction: Breast arterial calcifications (BAC) seen in mammogram are calcifications of the internal mammary artery. Atherosclerosis, in general, is an independent predictor of acute coronary, cerebrovascular and other vascular diseases. We evaluated the association between common carotid artery intima media thickness (C-IMT) in patients with and without breast arterial calcifications (BAC) on mammogram.Methods: This case control study included 108 women who underwent mammographic examination of breast in department of Radiology, TUTH, Maharajgunj, Kathmandu, Nepal. Cases were defined as patients with BAC on mammogram and matched controls without BAC were selected after obtaining ethical clearance from the Institutional Review Committee. Grading of BAC was done. Mean IMT of bilateral Common Carotid Artery (CCA) in cases and controls was measured on sonography. All the relevant data were entered in predesignated proforma and the findings tabulated. The mean IMT was calculated in cases and controls and compared using SPSS statistics. The null hypothesis was tested using independent t test.Results: The age ranged from 34 to 78 years. Maximum number of cases had grade BAC score of 1. The mean value of IMT in right CCA was 0.79mm and 0.57mm, that of left CCA was 0.78mm and 0.57 mm in cases and controls, respectively. The mean IMT was higher in patients with higher BAC score. Null hypothesis was rejected by independent t test and odd’s ratio was> 1, showing significance of association between vascular calcification in breast and CCA IMT.Conclusions: Our study shows a significant association between the BAC and intima media thickness of CCA, latter being higher in patients with BAC and increasing with grade.